Molecular genecology of temperature response in Lolium perenne: 1. Preliminary analysis to reduce false positives - Hamilton, Ruaraidh Sackville; Skøt, L.; Chorlton, K.H.; Thomas, I.D.; Mizen, S. (Wiley, 2002)
Molecular genecology is the study of geographical clines in frequencies of molecular markers and their relationship to ecological clines in environmental conditions. This study outlines the principles underlying the selection of populations, focusing on avoiding ‘false positives’— noncausal correlations between allele frequency and the environment. The principles are illustrated by identifying a set of populations of Lolium perenne for the study of temperature responses. The selected set of populations encompasses a 20 °C range in mean January temperature. Their freezing tolerance shows a linear trend with winter temperature, LT50 decreasing by 0.25 °C for each 1 °C reduction in mean January temperature.